Coronavirus Disease 2019 Vaccine Impact on Rates of Severe Acute Respiratory Syndrome Coronavirus 2 Cases and Postvaccination Strain Sequences Among Health Care Workers at an Urban Academic Medical Center: A Prospective Cohort Study. (17th September 2021) - Bouton, Tara C; Lodi, Sara; Turcinovic, Jacquelyn; Schaeffer, Beau; Weber, Sarah E; Quinn, Emily; Korn, Cathy; Steiner, Jacqueline; Schechter-Perkins, Elissa M; Duffy, Elizabeth; Ragan, Elizabeth J; Taylor, Bradford P; et al.
Abstract: Background: Coronavirus disease 2019 (COVID-19) vaccine trials and post-implementation data suggest that vaccination decreases infections. We examine vaccination's impact on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) case rates and viral diversity among health care workers (HCWs) during a high community prevalence period. Methods: In this prospective cohort study, HCW received 2 doses of BNT162b2 or mRNA-1273. We included confirmed cases among HCWs from 9 December 2020 to 23 February 2021. Weekly SARS-CoV-2 rates per 100, 000 person-days and by time from first injection (1–14 and ≥15 days) were compared with surrounding community rates. Viral genomes were sequenced. Results: SARS-CoV-2 cases occurred in 1.4% (96/7109) of HCWs given at least a first dose and 0.3% (17/5913) of HCWs given both vaccine doses. Adjusted rate ratios (95% confidence intervals) were 0.73 (.53–1.00) 1–14 days and 0.18 (.10–.32) ≥15 days from first dose. HCW ≥15 days from initial dose compared to 1-14 days were more often older (46 vs 38 years, P = .007), Latinx (10% vs 8%, P = .03), and asymptomatic (48% vs 11%, P = .0002). SARS-CoV-2 rates among HCWs fell below the surrounding community, an 18% vs 11% weekly decrease, respectively ( P = .14). Comparison of 50 genomes from post–first dose cases did not indicate selection pressure toward known spike antibody escape mutations. Conclusions: Our results indicate an early positive impact of vaccines on SARS-CoV-2 case rates. Post-vaccination isolates did not show unusual genetic diversity or selection for mutations of concern. Abstract : Cases of SARS-CoV-2 among health care workers dropped rapidly with COVID-19 vaccination. Sequencing 50 breakthrough infections (overwhelmingly in 14 days after first dose) showed no clear sign of any differences in spike protein compared with time-matched, unvaccinated control sequences.